FEATURES OF SCABIES AND NEW APPROACHES TO ITS DIAGNOSIS AND TREATMENT IN THE REGION OF ANDIJAN - Mamatkhujaev Azamat Saidakbarovich (Scholar Express Journals, 2024)
The article presents a review of domestic and foreign medical literature, reflecting the current state of epidemiology, various clinical forms of scabies and the reasons for failures in its treatment.
Keywords: Scabies; Clinical Picture; Epidemiology; Treatment